Natural Area Weeds: Invasive Solanum spp. in Florida - L. T. Markle; William A. Overholt; Kenneth A. Langeland (EDIS, 2009)
SS-AGR-312, a 7-page illustrated fact sheet by L. T. Markle, W. A. Overholt, and K. A. Langeland, provides a guide to differentiate the invasive Solanum species, information about the ecology and management of each species, and information on Solanum capsicoides All., which can easily be confused with some of the invasive Solanum species. Includes references. Published by the UF Department of Agronomy, November 2008.